Purchase Intention of Halal Lip Cosmetics on Shopee among Youth Generation: An Investigation using Theory of Planned Behavior - Hanafiah, Ali; Laylatushufa, Nazilah; Ahmad, Fauziah Sh; Wibowo, Mas Wahyu; Nusraningrum, Dewi (Jurnal Manajemen Teknologi, 2023)
Abstract. As the world's largest Muslim-majority country, Indonesia presents its Islamic Economic Landscape in the 2019-2024 Sharia Economic Masterplan, which features halal cosmetics as one of the six highlighted clusters. The leading research shows that Muslim women have expressed concerns regarding cosmetic product compliance with halal standards. This study aims to explore the specific purchase intentions of Indonesian Muslim young women regarding halal lip cosmetics, focusing on their preferences and behavioral intentions on a popular e-commerce platform (Shopee). This research object is Generation Z and Y Muslim women in Indonesia, totaling 210 respondents. This research employs a quantitative data analysis approach using the Smart-PLS 3.2.9 Variance-Based Structural Equation Model. All hypotheses significantly and positively affect the purchase intention of halal lip cosmetics on shopee. The findings indicate that the Theory of Planned Behavior (TPB) variables (Attitude- SubjectiveNorm- Perceived Behavioral Control) can still be applied to examine the behavioral intentions of young Indonesian Muslim women regarding the purchase of halal lip cosmetics. In addition, the extended variables of TPB (E-WOM and Brand Image) emerged as positive predictors of behavioral intention, indicating that further investigation of other variables as potential extensions of TPB is needed. Keywords: E-WOM, brand image, theory of planned behavior, purchase intention, shopee, halal lip cosmetics. Abstrak. Sebagai negara berpenduduk mayoritas Muslim terbesar di dunia, Indonesia menampilkan Lanskap Ekonomi Islam dalam Masterplan Ekonomi Syariah 2019–2024, yang menampilkan kosmetik halal sebagai salah satu dari enam klaster yang disorot. Penelitian terkemuka menunjukkan bahwa wanita Muslim telah menyatakan keprihatinannya mengenai kepatuhan produk kosmetik terhadap standar halal. Penelitian ini bertujuan untuk mengeksplorasi niat pembelian dari Muslimah muda Indonesia terkait kosmetik bibir halal, dengan fokus pada preferensi dan niat perilaku mereka pada platform e-commerce populer (Shopee). Objek penelitian ini adalah generasi Z dan Y Muslimah di Indonesia sebanyak 210 responden. Penelitian ini menggunakan metode kuantitatif dengan menggunakan pendekatan analisis data menggunakan Smart-PLS 3.2.9 Variance Based Structural Equation Model. Seluruh hipotesis berpengaruh terhadap niat pembelian kosmetik bibir halal di Shopee secara signifikan dan positif. Temuan menunjukkan bahwa variabel Theory of Planned Behavior (TPB) (Attitude- SubjectiveNorm- Perceived Behavioral Control) tetap dapat diterapkan untuk menguji niat Muslimah muda Indonesia mengenai pembelian kosmetik bibir halal. Selain itu, variabel yang diperluas dari TPB (E-WOM dan Citra Merek) muncul sebagai prediktor positif terhadap niat berperilaku, yang menunjukkan bahwa diperlukan penyelidikan lebih lanjut terhadap variabel lain sebagai potensi perluasan TPB. Kata kunci: E-WOM, citra merek, theory of planned behavior, niat beli, shopee, kosmetik bibir halal